(untitled) (Research, Society and Development, 2022)
The urban development policy goes through the property right that must take into account the set of rules that aim to discipline the growth and evolution of the city, registers that constitutionally urban property needs to fulfill its social function. The subdivision of land, as an urban area planning, constitutes a public function and prevails over private interests. This research aims to study territorial development in the Metropolitan Region of Goiânia, presenting the historical aspects, important regulations on the subject since the creation of that Region, highlighting notable points of the allotment laws of the municipalities of this cluster and the Master Plan of Goiânia. regarding the instrument of land tenure regularization for the social inclusion of low-income families. In order to answer about the Territorial Development aspect and its consequences: Where do we come from? Where are we? and What do we want? The study was supported by bibliographical, exploratory and documentary references, being the main source for collecting information, analyzing data from the Brazilian Institute of Geography and Statistics regarding the subnormal agglomerates of the aforementioned Metropolitan territory.